Impact of aluminum wire and ribbon bonding technologies on D2PAK package reliability during thermal cycling applications. Issue 9 (August 2015) - Jacques, S.; Leroy, R.; Lethiecq, M.
Abstract: This paper highlights the impact of bonding techniques (Al wire and Al ribbon) on the aging of Schottky diodes, assembled in D 2 PAK package, subjected to temperature cycling. The experimental test results coupled with failure analyses exhibit a better robustness and a lifetime about 2.3 times higher for the ribbon bonding assembly. A higher contact surface, the low loop profile and stiffness of ribbons allow slowing down crack initiation and propagation between the Al bond and Al metallization on the top of the silicon die.